Kualitas Pelayanan Publik Sistem Administrasi Manunggal Satu Atap (Samsat) Provinsi Banten - Anggraini, Yusniah; Rahayuningsih, Yunia (Jurnal Bina Praja, 2021)
One Roof System, as one of the administrative services in Banten Province, was created to accommodate the community's needs for good public services. The one roof system office is required to always improve its performance to achieve excellent service while at the same time providing satisfaction to the community. Based on this, the measurement of community satisfaction is something that the one roof system Office needs to do. This study aims to determine the quality of public services in 8 one roof system offices in Banten Province as measured by the Community Satisfaction Index (IKM) and analyze the quality of One Roof System services in Banten Province. This study used mixed-method research. Data were obtained through questionnaires, observation, and documentation. The sample was 240 people, which is determined by the quota sampling technique. The results showed that quantitatively, the quality of public services at 8 one roof system offices in Banten Province based on the Community Satisfaction Index reached 75.66, which qualitatively was categorized as good. Although it has been categorized as good, several elements need serious attention from the ten elements assessed, namely service time, service fees, officer behavior, complaint handling, and supporting elements. Improvements in service improvement are carried out by paying online taxes through the Samsat Banten Hebat (SAMBAT) application, but it was still not optimal, constrained by the quality of human resources and the creation of digital culture.